2021
DOI: 10.1183/13993003.00979-2021
|View full text |Cite
|
Sign up to set email alerts
|

Steroid use in elderly critically ill COVID-19 patients

Abstract: This secondary analysis of the COVIP study shows a higher 30-day-mortality in critically ill elderly COVID-19 patients who received steroids as part of their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 8 publications
2
50
0
1
Order By: Relevance
“…Second, mortality was significantly higher in elderly patients receiving corticosteroids and corticotherapy was independently associated with increased mortality. These results are similar to previously reported data questioning the routine use of corticosteroid treatment in elderly COVID-19 patients [ 41 ]. Even though this study was not specifically designed to evaluate the effects of corticosteroids in elderly patients, the results suggest that this treatment might not be as beneficial as expected from the results in younger patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, mortality was significantly higher in elderly patients receiving corticosteroids and corticotherapy was independently associated with increased mortality. These results are similar to previously reported data questioning the routine use of corticosteroid treatment in elderly COVID-19 patients [ 41 ]. Even though this study was not specifically designed to evaluate the effects of corticosteroids in elderly patients, the results suggest that this treatment might not be as beneficial as expected from the results in younger patients.…”
Section: Discussionsupporting
confidence: 92%
“…In this cohort, corticosteroid prescription was independently associated with mortality in the multivariate analysis (Table 3). There are some previously published data suggesting similar results, as a secondary analysis of the COVIP study having found a higher 30-day-mortality in critically ill COVID-19 patients, aged 70 years or older, who received steroids as part of their treatment [41]. However, there is no recommendation yet for the differentiated treatment of elderly patients.…”
Section: Corticosteroid Prescription In Elderly Patientsmentioning
confidence: 74%
See 1 more Smart Citation
“…Even before COVID-19, the impact of corticosteroids has been inconsistent in other causes of pneumonia including influenza, community-acquired pneumonia (CAP), and the original severe acute respiratory syndrome (SARS) [ 8 , 23 26 ]. The impact of corticosteroids likely depends on multiple factors, including patient age and other characteristics, heterogeneity in host response to infection, etiology of pneumonia, time since onset of infection and presence and severity of acute respiratory distress syndrome (ARDS) [ 8 , 10 , 27 31 ]. While corticosteroids may decrease host inflammatory response, potentially modulating lung injury, they may also have harmful side effects or unintended consequences on adaptive immune responses that may be important to resolution of infection and increase risk of secondary infection.…”
Section: Discussionmentioning
confidence: 99%
“…Un patient non fragile de plus de 75 ans avait une meilleure survie à 3 mois qu’un patient fragile de moins de 75 ans [28] . L’impact des traitements corticoïdes était opposé à ce qui est rapporté chez des patients plus jeunes avec une surmortalité soulignant l’absolue nécessité d’avoir des études incluant les patients âgés [34] .…”
Section: Particularités De La Covid Chez Les Patients âGésunclassified